Modifying games for improved aerobic fitness and skill acquisition in youth - Cronin, J.; Harrison, C.; Lloyd, R. S.; Spittle, M. (Strength and Conditioning Journal, 2017)
By combining technical and tactical game components with appropriate physical loading, modified games can provide an ideal environment for young athletes to develop aerobic fitness, while at the same time accumulate precious hours of technical skills development. Furthermore, modified games provide an opportunity for players to develop their decision-making and problem solving skills under stressful physical loads, which are critical factors in successful long-term player development. This article discusses those constraints believed important in optimizing aerobic fitness and skill acquisition in youth using a modified games approach. For a video abstract describing this issue, see video, supplemental digital content 1, http://links.lww.com/scj/a203.